Integrated Dating of the Construction and Restoration of the Modena Cathedral Vaults (Northern Italy): Preliminary Results. Issue 3 (16th June 2020) - Tirelli, G; Lugli, S; Galli, A; Hajdas, I; Lindroos, A; Martini, M; Maspero, F; Olsen, J; Ringbom, Å; Sibilia, E; Caroselli, M; Silvestri, E; et al.
ABSTRACT: After the last damaging earthquake in 2012, an anti-seismic reinforcement project of the cathedral of Modena was designed giving us the opportunity to investigate and date the building materials. Radiocarbon ( 14 C), optically stimulated luminescence (OSL), and thermoluminescence (TL) dating techniques were performed on the vaults with the aim to (1) clarify the construction timing, (2) define the history of the restorations, and (3) explore the possible correlation of the main restoration works to the earthquake chronology deduced from the historic catalog. Preliminary results show that medieval older bricks were reused for most of the original construction. Only lime and non-gypsum mortar was used for the original construction in the 15th century and for later repair of damage caused by earthquakes in the 16th and 17th centuries. Gypsum mortar was used for later repair in the 18th century. The results show much stronger damage due to earthquakes than previously thought.